Teaching Reading Strategies Implemented on Student's Reading Comprehension at a Vocational High School - Ghozali, Muhamad Afifuddin; Adi, Waskito (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
Reading is one of the four necessary important language skills among those skills in learning English as a second or foreign language (ESL/EFL). Pressley & Afflerbach (1995) cited in Erlando (2017) states that good readers should not solely read the text to comprehend a text, but also it should be connected with past experiences. It will ease the students to understand reading material when the knowledge is absorbed first. The research reflects upon teaching reading strategies introduced by Vacca & Vacca (1999) in analyzing the teaching strategies implemented on students’ reading comprehension at a vocational high school, SMK Negeri 2 Batu. A case study is used with the aim to describe teaching reading strategies applied by the teacher by conducting an interview with the English Teacher and observing teaching reading strategies implementation in class at SMK Negeri 2 Batu. The subject of the research is first-year students of AHP A, SMK Negeri 2 Batu consisting of 28 students. It is found that three teaching strategies, scaffolding strategy, question and answer relationship (QARs), and think-aloud strategy, are implemented sequentially.